1993
DOI: 10.1007/bf00857517
|View full text |Cite
|
Sign up to set email alerts
|

Physiological assessment of aspects of autonomic function in patients with secondary progressive multiple sclerosis

Abstract: A detailed non-invasive study of systemic and regional haemodynamic responses to a range of autonomic tests which assess sympathetic and parasympathetic pathways (mental arithmetic, cutaneous cold, isometric exercise, deep breathing, Valsalva manoeuvre and head-up tilt) were performed in ten patients with secondary progressive multiple sclerosis and ten age- and sex-matched healthy normal subjects (controls). Blood pressure rose in controls during the pressor tests and was maintained during tilt. In six out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 15 publications
5
33
0
Order By: Relevance
“…The proportion of patients with two or more abnormal test results (which is generally taken to establish significant autonomic dysfunction [21]) ranged from 10% [38] to 50% [34]. The majority of studies revealed an involvement of both sympathetic and parasympathetic pathways, with the heart rate response to deep breathing [2,23,32,38] and the blood pressure response to sustained HG [27,32,36,38] being most frequently impaired. However, no group differences in the deep breathing test were found by other authors [8,11,22] or in the present study.…”
Section: Cardiovascular Reflex Testsmentioning
confidence: 98%
See 2 more Smart Citations
“…The proportion of patients with two or more abnormal test results (which is generally taken to establish significant autonomic dysfunction [21]) ranged from 10% [38] to 50% [34]. The majority of studies revealed an involvement of both sympathetic and parasympathetic pathways, with the heart rate response to deep breathing [2,23,32,38] and the blood pressure response to sustained HG [27,32,36,38] being most frequently impaired. However, no group differences in the deep breathing test were found by other authors [8,11,22] or in the present study.…”
Section: Cardiovascular Reflex Testsmentioning
confidence: 98%
“…A number of investigations have focused on cardiovascular reflex tests [2,11,12,16,17,23,24,26,36,38], but these have provided conflicting data about the frequency and distribution of cardiovascular autonomic dysfunction in MS. More than 50% of the patients observed by Pentland et al [26], Nordenbo et al [24], Gallai et al [12], and Anema et al [2] showed abnormal responses on one or more tests, while much lower frequencies were found by Linden et al [16,17], Ferini-Strambi et al [8], Frontoni et al [11] and Nasseri et al [23]. The proportion of patients with two or more abnormal test results (which is generally taken to establish significant autonomic dysfunction [21]) ranged from 10% [38] to 50% [34].…”
Section: Cardiovascular Reflex Testsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is therefore reasonable to suspect that the autonomic neural regulation of beat-to-beat fluctuations in blood pressure by the arterial baroreflex is altered in individuals with MS. Prior investigations on cardiovascular autonomic dysfunction in MS have mostly been descriptive in nature, failing to provide mechanistic insight (Acevedo et al 2000;Anema et al 1991;Flachenecker and Reiners 2005;Flachenecker et al 1999;Frontoni et al 1997;Nasseri et al 1998;Pentland and Ewing 1987;Racosta et al 2015;Senaratne et al 1984;Thomaides et al 1993). To our knowledge, there has been only one attempt to assess baroreflex control in individuals with MS. Utilizing dynamic sinusoidal neck suction to induce carotid hypertension, Sanya et al (2005) demonstrated baroreflex impairments in persons with MS.…”
Section: New and Noteworthymentioning
confidence: 99%
“…Arterial baroreflex control of blood pressure is essential for short-term (i.e., beat-to-beat) regulation of blood pressure (Smit et al 2002;Timmers et al 2003). The arterial baroreceptor reflex prevents large fluctuations of arterial blood pressure by providing the central nervous system with continuous information from stretch-sensitive baroreceptors originating at the carotid sinus and aortic arch.…”
mentioning
confidence: 99%